2017
DOI: 10.1177/1099636216686649
|View full text |Cite
|
Sign up to set email alerts
|

Parametric study on factors influencing the stiffness of honeycomb sandwich panels using impulse excitation technique

Abstract: Metallic thermal protection systems are used to protect the airframe and pay load from aerodynamic and aerothermal heating in hypersonic cruise vehicles that are powered with advanced scramjet engines. Metallic thermal protection systems is a composite structure that contains honeycomb sandwich panels at the top and bottom and a variety of thermal insulating materials placed in between them. Several design factors influence the structural and thermal performance of the honeycomb sandwich panels. Panel bending … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…• It has been observed that honeycomb core cell size doesn't have a significant effect on the stiffness properties of a composite sandwich panel. This is in accordance with the observations made by Kiran et al [21] and Zhang and Ashbey [22] that the core cell size of a honeycomb core has negligible effect on the stiffness property of a composite sandwich panel. • Also it has been found that with increased panel width the stiffness of composite panel increases significantly.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…• It has been observed that honeycomb core cell size doesn't have a significant effect on the stiffness properties of a composite sandwich panel. This is in accordance with the observations made by Kiran et al [21] and Zhang and Ashbey [22] that the core cell size of a honeycomb core has negligible effect on the stiffness property of a composite sandwich panel. • Also it has been found that with increased panel width the stiffness of composite panel increases significantly.…”
Section: Discussionsupporting
confidence: 93%
“…Lister [18] also observed that Core ribbon orientation has an important role in a sandwich beam's bending behavior. Kiran et al [21] described that core cell size and core sheet thickness has negligible effect i.e. they contribute only 4% towards the stiffness per unit weight as compared to other design factors.…”
Section: Introductionmentioning
confidence: 99%
“…The lightweight composite sandwich structure provided better impact resistance, maximum energy absorption, specific strength and stiffness as well as protection against blast [1][2][3][4][5]. Sandwich structures with a square honeycomb core are most commonly used for the protective layer against blast loading [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The lightweight composite sandwich structure provided better impact resistance, maximum energy absorption, specific strength and stiffness as well as protection against blast [1][2][3][4][5]. Sandwich structures with a square honeycomb core are most commonly used for the protective layer against blast loading [2][3][4][5][6][7]. The numerical results show that the sandwich failure behaviour undergoes large elastic deformation, shear band and bending failure at the end [2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation